HAK DAN KEWAJIBAN ORANG TUA TERHDAP ANAK SETELAH PUTUSNYA PERKAWINAN (STUDI KOMPARATIF ANTARA UU NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN UU NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK) - Nasrah; Zubair, Asni (UIN Palopo, 2022)
ABSTRACTThe purpose of this study is to know the rights and obligations of a parent to a child after the breakup of a marriage and to know the similarities and differences the parental obligations to the child in bill no.1 year 1974 on Jo's marriage, 2019 year no. 16 on marriage and 2014 no. 35 on child protection Research indicates that the first marriage when children are born, it not only brings upon a couple the rights and obligations but also raises the rights and obligations between the husband and wife on the one hand but also in relation to his rights and duties toward his children.In article 45 of 1974's law no. 1, it states that both parents are obligated to care well for and educate their children and vice versa. Second, the statute of marriage no.1 year 1974 mentions chapter 41: both mother and father remain under obligation to care for and educate their children, based solely on the child's interest. While in point b